Performance of photovoltaic module at different tilt angles in Perlis, Northern Malaysia - Ismail, Daut, Prof. Dr.; Muhammad Irwanto, Misrun; Ezzani, M.; Mohd Irwan, Yusoff (Praise Worthy Prize, 2012)
Link to publisher's homepage at http://www.praiseworthyprize.com/